Congenital Smooth Muscle Hamartoma Obscuring the Cornea. (8th May 2021) - Bean, Andrew; Al-Bouri, Abdullah; Bradford, Geoffrey; Mauger, Thomas
Abstract : Congenital smooth muscle hamartoma is a benign proliferation of smooth muscle that most commonly presents in the lumbosacral area or proximal extremities. Although exceedingly rare, congenital smooth muscle hamartomas have been reported to occur in ocular structures such as the brow, eyelid, and conjunctival fornix. This case describes an atypical congenital bulbar lesion in a newborn male which obscured the cornea. The lesion, which appeared to originate from the bulbar conjunctiva and/or the limbus, was excised at 5 months of age. Pathologic evaluation was consistent with congenital smooth muscle hamartoma. The authors of this report believe it is the first to describe a patient with a congenital smooth muscle hamartoma of the bulbar conjunctiva/limbus.